A Ramp Metering Strategy for Rapid Congestion Recovery. (3rd November 2014) - Jiang*, Rui; Chung, Edward
Abstract Recurrent congestion caused by high commuter traffic is an irritation to motorway users. Ramp metering (RM) is the most effective motorway control means for significantly reducing motorway congestion. However, given field constraints (e.g., limited ramp space and maximum ramp waiting time), RM cannot eliminate recurrent congestion during the increased long peak hours. This article, therefore, focuses on rapid congestion recovery to further improve RM systems: that is, to quickly clear congestion in recovery periods. The feasibility of using RM for recovery is analyzed, and a zone recovery strategy for RM is proposed. Note that this study assumes no incident and demand management involved, that is no rerouting behavior and strategy considered. This strategy is modeled, calibrated, and tested in the northbound model of the Pacific Motorway, Brisbane, Australia, in a microsimulation environment for recurrent congestion scenario, and evaluation results have justified its effectiveness.